2006
DOI: 10.1002/tea.20141
|View full text |Cite
|
Sign up to set email alerts
|

Science inquiry and student diversity: Enhanced abilities and continuing difficulties after an instructional intervention

Abstract: This study examines elementary students' abilities to conduct science inquiry through their participation in an instructional intervention over a school year. The study involved 25 third and fourth grade students from six elementary schools representing diverse linguistic and cultural groups. Prior to and at the completion of the intervention, the students participated in elicitation sessions as they conducted a semistructured inquiry task on evaporation. The results indicate that students demonstrated enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 50 publications
3
49
0
2
Order By: Relevance
“…Repeated exposure to standards-based instruction supported by highly specified and developed curriculum leads to additional learning gains, at least when science inquiry is pursued at multiple grade levels. This supports work by Lee et al (2006), who also found cumulative effects from continuing inquiry science instruction across grade levels on proximal curriculum-aligned assessments. This indicates that the more inquiry science instruction we are able to provide to students during their schooling, the larger the learning growth we will expect to see in achievement.…”
Section: Individual Student Achievementsupporting
confidence: 84%
See 1 more Smart Citation
“…Repeated exposure to standards-based instruction supported by highly specified and developed curriculum leads to additional learning gains, at least when science inquiry is pursued at multiple grade levels. This supports work by Lee et al (2006), who also found cumulative effects from continuing inquiry science instruction across grade levels on proximal curriculum-aligned assessments. This indicates that the more inquiry science instruction we are able to provide to students during their schooling, the larger the learning growth we will expect to see in achievement.…”
Section: Individual Student Achievementsupporting
confidence: 84%
“…Lee, Buxton, Lewis, and LeRoy (2006) measure the impact of an urban instructional intervention in grades 3-5 using matched pre-and post-tests, and find substantial learning gains. Their data also suggests a cumulative effect of the intervention as students participate over several years.…”
Section: Assessmentmentioning
confidence: 99%
“…Inquiry in this manner is said to be an active learning process and 'something that students do, not that is done to them' (NRC 1996, 2). In the present study, inquiry is considered to be any combination of the activities described as inquiry by Cuevas et al (2005), Lee et al (2006), and NRC (1996, 2000. These are: identifying or refining questions, planning investigations, implementing investigative plans, proposing explanations and comparing explanations with scientific knowledge (concluding), and communicating reports.…”
Section: Scientific Inquirymentioning
confidence: 99%
“…Despite this, the research is scant specifically regarding EL and EC students and the exploration of the relationship between academic language and overarching conceptual understanding in science. However, a few researchers (e.g., [12,13,[26][27][28][29][30]) have provided solid evidence that inquiry-based instructions increase, in particular, ELs' and ECs' conceptual understanding of science, particularly when literacy is connected to science instruction. The inquiry-based instruction referred to in our study includes engaging ELs and ECs in practices such as asking questions, planning investigations, developing models, and interpreting data, all while promoting language and literacy skills.…”
Section: Literacy-infused Inquiry-based Science For Els and Ecsmentioning
confidence: 99%